Independents in Irish party democracy - Weeks, Liam (Book collections on Project MUSE., 2017)
This book examines the phenomenon of the independent politician, believed to be extinct in most political systems. It is very much alive and well in Ireland, and has experienced a considerable resurgence in recent years. Independents won a record number of seats in 2016 and had three ministers appointed to cabinet. This presence is very unusual from a comparative perspective, and there are more independents in the Irish parliament than the combined total in all other industrial democracies. The aim of this book is to explain this anomaly, how and why independents can endure in a democracy that is one of the oldest surviving in Europe and has historically had one of the most stable party systems. --